The effects of microplastic on the thermal profile of sand: implications for marine turtle nesting grounds - Mariana M. P. B. Fuentes; Valencia Beckwidth; Matthew Ware (Frontiers in Marine Science, 2023)
Introduction Microplastics (i.e., plastic debris smaller than 5mm) found in coastal areas can impact the marine habitat used by endangered species since they may alter sand properties including temperature and permeability. Such alterations may pose a significant threat to marine turtle populations as nest productivity, sexual development, and hatchling fitness are dependent on conditions within the nest, which incubate in the sand. Given that there is a record of microplastic presence at marine turtle nesting sites, this study was conducted to explore the potential influence of microplastics on the thermal profile of sediment typical of marine turtle nesting habitat. Methods The experiment was conducted at the Florida State University Coastal and Marine Laboratory where the temperatures of containers of sand mixed with 5-30% v/v of either black or white microplastics were recorded from July to September 2018. Results The addition of microplastics in the sand resulted in an increase in temperature – 0.017°C for each 1% v/v increase in microplastic. However, the color of the microplastic did not have a significant effect on sand temperature. Overall, the container with 30% v/v black particles had the highest mean temperature increase of 0.58°C (± 0.34°C) over the control. Discussion The results obtained from this study indicate that extreme concentrations of microplastics could be an issue for marine turtles as any changes in sand temperature may affect the sex ratio of hatchlings and/or alter nest productivity.